Process Optimization for the Preparation of Activated Coke from Industrial Waste Using Response Surface Methodology - Juanqin Xue, Xiande Jing, Shudi Hu, Yuhong Tian, Yonghui Song and Xinzhe Lan (Nature Environment and Pollution Technology, 2019)
Fine blue-coke and direct liquefaction residue of coal are byproducts in the process of coal chemical production. They were taken as raw materials for the preparation of activated coke by the activation of carbon dioxide. The conditions (activation temperature, activation time and carbon dioxide flow rate) for activated coke preparation were optimized by response surface methodology (RSM). Results showed that activation temperature and activation time had a significant effect on the activated coke iodine adsorption value. The synergistic effect of activation time and carbon dioxide flow had a great influence on iodine adsorption value of activated coke. RSM optimization experiment obtained the optimum activation conditions were activation temperature of 850°C, activation time of 90min and carbon dioxide flow rate of 60 mL/min. Under these conditions, the obtained activated coke iodine adsorption value can reach 401 mg/g, which could meet the needs of industrial desulphurization.